Literasi Kesehatan pada Pasien Diabetes Mellitus Tipe 2 - Dita Hanna Febriani (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Health literacy can play an important role in the quality of the provided care since patients with T2DM need long-term and high level of complex care. Inadequate literacy patients with DM related to less knowledge about diabetes and poorer health outcome. Objective: This study aimed to examine health literacy among patients with type 2 diabetes mellitus and its related factors. Methods: This study used cross sectional design. The respondents recruited with a convenience sampling in outpatient internal medicine department in a hospital located in Sleman regency from September 2017 to January 2018. The Charlson Comorbidity Index and the European Health Literacy Survey - Questionnaire 47 were employ. Data analysis involved descriptive and bivariate analysis. Results: A hundred and fifty two subjects enrolled in this research. The average score of health literacy was 29.5 (SD = 3.4). Factors related with health literacy were total number of complications (r = -.26; p = .001), education (p = .010) and monthly income (p = .000). Conclusion: Problematic health literacy has been found to be prevailing in patients with type 2 diabetes mellitus in Yogyakarta, Indonesia. Total number of complications, education, and monthly income were significantly correlated with health literacy in this population.